Implementasi Metode Team-Based Project Dalam Pembelajaran Manajemen Pelayanan di Jurusan Pendidikan Ekonomi Universitas Negeri Semarang - Susanti, Anis; Oktarina, Nina (JURNAL ADMINISTRASI KANTOR, 2022)
This study aims to analyze the implementation of the team-based project method in learning service management at the Department of Economic Education, Semarang State University. Learning after the pandemic encountered difficulties including the ability of students to develop aspects of skills. During online learning, learning is often focused on lecturers who explain, one of which is in learning service management. Team-based projects are implemented because students need to develop their problem - solving skills, especially in service management competencies. The team-based project method is implemented through the assignment of problem solving in organizational service management and is analyzed in the form of posters. This research uses descriptive qualitative approach. Data were analyzed with the Milles & Huberman model including data collection, data reduction and making conclusions. Sources of data obtained from observation, interviews and documentation. The results of the study show that students who have been passive in class and learning during the implementation of the team -base project become more active in developing skills in groups because they have their respective roles while analyzing the implementation of service management. Each group has different abilities in producing projects in the form of posters which are judged by speed, accuracy and tidiness.      Keywords : team-based projects; service management; poster.